IMPLEMENTATION OFÂ GUIDED DISCOVERYÂ MODEL USING LABORATORY ACTIVITIES IN ELASTICITY MATERIAL AT SECOND GRADE OF SMAN 1 KANDANGAN - SEPTIDA, VINTANIA (Inovasi Pendidikan Fisika, 2018)
Guided discovery models with laboratory activities is one of the learning that facilitates students to conduct a guided discovery. The results of interviews at SMAN 1 Kandangan found that 60% of the students gets score below the minimum passing score in the elasticity material which one of the factors is caused by the activity of the students during the learning process. Based on the above, the research implemented guided discovery model with laboratory activities for improve the activity of the students. The aims of research are describing the implementation of learning, improving learning outcomes, and student responses to elasticity materials. This research used quantitative research type with pre-experimental research design using one group pretesst-posttest design, with one experiment class and two replication classes. The data method used are observation, test, and questionnaire. The data obtained from pretest and posttest result were analyzed by normality test, homogeneity test, t test and normalized gain test. The result of research are: a) the implementation of the learning process in the three calsses that were observed from the teachers activity in two meetings is very well done; b) based on gain test analysis, the learning outcomes for all the three classes were increased with high category; c) the learning has received positive response from students with very good category. Based on the above explanation, the learning processes that are implemented using guided discovery model with laboratory activities can improve student learning outcomes. Keywords: guided discovery models, laboratory activities , learning result, elasticity.